A MOF-derived Co3O4/nitrogen-doped carbon composite for chlorine-assisted production of ethylene oxide. Issue 5 (14th February 2023) - Li, Tianlei; Liu, Hengzhou; Yu, Jiaqi; Chen, Yifu; Huang, Wenyu; Li, Wenzhen
Abstract : A MOF-derived cobalt oxide/nitrogen-doped carbon composite is prepared and it exhibits remarkable performance for chlorine-assisted ethylene oxide production. Abstract : Ethylene oxide (EO) is one of the most crucial materials in plastic industries. The traditional catalytic process requires high temperature and pressure to produce EO. A chlorine-assisted system has been reported to produce EO, but it required noble metal catalysts, which significantly increased the cost. In this work, a MOF-derived Co3 O4 /nitrogen-doped carbon composite (Co3 O4 /NC) prepared through a two-step calcination method exhibited remarkable chlorine evolution reaction (ClER) activity as compared with a commercial RuO2 catalyst, which can be attributed to the higher specific surface area and lower resistance of its porous structure and nitrogen-doped carbon. Furthermore, the Co3 O4 /NC maintained a stable potential and a high faradaic efficiency throughout the 10-hour electrolysis test.